PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON ASSETS TERHADAP HARGA SAHAM SEKTOR KIMIA YANG TERDAFTAR DI BEI - Handika Adinata Bangun; Januardin Januardin (Jurnal Manajemen Terapan dan Keuangan, 2022)
The orientation of this research is to be able to carry out analysis and also testing for the Debt to Equity Ratio, Current Ratio, and Return On Assets variables on the chemical sector stock price variables listed on the Indonesia Stock Exchange. For this study, the technique of collecting research data was found to be successful using purposive sampling and the number of samples was 17 companies from 73 populations. Chemical sector companies listed on the Indonesia Stock Exchange (IDX). For this research, the analytical model used is multiple linear regression. The results of this test test that the value of the R-square is worth 0.070, this indicates that there is a relationship involving business risk, capital structure, firm size, and firm value of 7.0%. The value of Adjusted R Square is 0.035. These results explain that the variables of firm size, capital structure, and also business risk can predict or clarify the firm value variable of 3.5%. For the test results, that the value of Fcount is higher than Ftable (4.036 > 2.73), with this, the independent variables of DER, CR and ROA simultaneously have an effect on stocks for chemical sector companies. Meanwhile, for the partial test, the Return on Assets is 0.38 which means that the independent variable has an influence on the Stock Price variable for Chemical Sector companies. Keywords: Current Ratio, Debt to Equity Ratio, Return On Assets and Stock Price.